Globalization and Family Values: Eroding Trends - Rahman, K. M. Atikur; Zhang, Dunfu (International Journal of Social and Administrative Sciences, 2017)
The paper focuses on globalization process and its impact on family structure and values. Globalization refers to an expedited process of uniformities, universalization and hybridization of materials and culture. It blends all types of socio-economic and cultural activities into a unique form. No society including a cultural structure can go forward without the touches of others in the interconnected and interdependent world. So, cultural conflict generates among all societal structures along with the diversity of global socio-cultural values. The study found some significant outcomes such as traditional extended families are breaking down into nuclear ones especially in the developing countries at recent times that were continued in the western societies for a long time. In addition, relations and value levels in the family environment are being worst leaving the marginal people (children and elderly persons) darkened. The paper aims to find out the bad impacts of globalization on family relations and behavioral values. Qualitative approach has been used herein to make the report fruitfully through the data collection process of content analysis that includes books, journal articles and media reports. Enjoyable material culture can also be taken forward along with bearing the family relations and values, wherein our roots and emotion generate to trigger us to sustainable living and that may be a social movement.